The family garden and culture. The space destined to medicinal plants in Xochipala, Guerrero - González Guinea, Amanda; González Santiago, María Virginia; Castellanos Suarez, José Alfredo (Revista Mexicana de Ciencias Agrícolas, 2018)
The family garden, which reflects the management and knowledge about the environment that surrounds a human group, is the space or the area surrounding the house. For Alvarez-Buylla and Lazos (1983), perennial and annual plants with different uses are cultivated and protected, either for self-consumption or for surpluses. Regarding this point, Gispert (1993) adds that in this site there are also social, biological and agronomic activities, which constitutes an economic unit of self-consumption at the door of the home. This article aims to value the family garden as a social inheritance. Although for Gutiérrez (2003), the family garden shows the relationship between social groups and plants, which persists despite the irruption of the development of civilizations or the proximity to large cities, Gispert (1993) expresses an aspect of the cultural identity of a human group in relation to nature. For Gispert (2005), this society-plant relationship is always dynamic; on the part of society, cultural, ideological, political and economic phenomena intervene, and on the part of the plant, the environment with its biomes and floras. To affirm that the family garden is part of the cultural identity of a social group, it is necessary to document and study the functions of said system and the management of plant diversity, to understand the relationship that exists between a social group and the environment that surrounds it, and finally understand that all of the above is part of the culture and identity of a community.
Keywords: culture, family garden, traditional medicine and social heritage, Xochipala